THE DETERMINATION OF PORE SIZE DISTRIBUTION AND SURFACE AREA FROM ADSORPTION ISOTHERMS - Eva Voigt (My University, 1954)
Theoretical isotherms have been developed which when com pared to experimental isotherms showing hysteresis, allow the calculation of pore size, pore size distribution and surface area of the sorbent. Interpretation of some experimental iso therms obtained with porous vycor glass shows that this system can best be represented by the ’’ink bottle” pore model with a Gaussian distribution of pore sizes. The mean pore radius of the porous glass is about two thirds of the Kelvin radius, and the surface area about twice that obtained from the B.E.T. theory. The Kelvin radius is interpreted as a weighted aver age, but the B.E.T. surface area appears more fundamentally different. As a consequence of the present theory multilayer adsorption, as opposed to capillary condensation^seems highly improbable on porous glass